2011
DOI: 10.3402/ijch.v70i2.17802
|View full text |Cite
|
Sign up to set email alerts
|

Obesity risks: towards an emerging Inuit pattern

Abstract: Objectives. The aim of this study was to provide analytical overviews of anthropometric measurements and their relationships with type 2 diabetes and cardiovascular disease (CVD) risk factors within the Inuit population, given that few studies have focused on this issue. Study design. Cross-sectional study. Methods. Anthropometric and biological data were obtained from 867 Inuit participants from Nunavik (≥18 years). Results. Obesity prevalence for men and women, respectively, was 25.1% and 31.3% according to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…Our data on prevalence of obesity are in line with previous studies of Inuit women (28,29). The cross-sectional International Polar Year Inuit Health Survey for adults in 2007–2008 showed that 41.6% of Canadian Inuit women had a BMI ≥30 kg/m 2 (30).…”
Section: Discussionsupporting
confidence: 92%
“…Our data on prevalence of obesity are in line with previous studies of Inuit women (28,29). The cross-sectional International Polar Year Inuit Health Survey for adults in 2007–2008 showed that 41.6% of Canadian Inuit women had a BMI ≥30 kg/m 2 (30).…”
Section: Discussionsupporting
confidence: 92%
“…All means were weighted to achieve population representativeness. Hence, the number of participants is indicated for informational purposes only.bp-Values based on a Student's t-test except for physical activity, smoking, drinking and education level which were determined using the Chi-square test in SAS.cThese data have already been reported in a previous publication (3). …”
Section: Resultsmentioning
confidence: 99%
“…This shift away from the traditional Inuit lifestyle has been associated with an increased prevalence of coronary heart disease (CHD) risk factors such as obesity (2,3), high blood pressure (BP) (2) and diabetes (4). High-sensitivity C-reactive protein (hs-CRP), a pro-inflammatory marker that has previously been shown to independently predict CHD outcomes in Caucasian populations (5,6), has recently been positively associated with cardiovascular disease (CVD) prevalence and carotid intima media thickness in the Inuit population of Alaska (7,8).…”
mentioning
confidence: 99%
“…Inuit body build differs from that of Caucasians in that Inuit have larger torsos and shorter limbs (15,16). This increases BMI independent of the degree of body fat as the torso carries more weight per centimetre than legs (17), and 31% of young, fit hunters in Greenland investigated around 1963 were classified as overweight when using the WHO cut-off points (10).…”
Section: Body Build and Bmi In Inuitmentioning
confidence: 98%